Comparative Analysis of WBC-Derived Inflammatory Markers in Cavitary and Non-Cavitary Sputum-Positive Tuberculosis - Moorthy, Swathy; Bhaskar, Emmanuel; S, Shivakumar; SIlambanan, Santhi (Shahroud Journal of Medical Sciences, 2025)
Background: Tuberculosis (TB), as an infectious disease, has consistently topped the list in any discussions owing to its spectrum of manifestations, morbidity, and mortality. The current diagnostic procedures are time consuming and cumbersome. Hence, there has been a constant search for highly sensitive and specific biomarkers with less turn-around-time as well as maintaining sensitivity and specificity. The current study aimed to examine the role of WBC and their derived inflammatory markers in sputum-positive active pulmonary tuberculosis (PTB) patients with and without cavity. Methods: The study was conducted among sputum-positive PTB patients (n=27) who were further grouped into cavitatory (n=15) and non-cavitatory (n=12). The presence of cavities in the lungs were identified by chest X-ray. The study was conducted in the Department of General Medicine at a tertiary hospital in South India. Ethics approval was obtained from the institutional ethics committee (IEC), and written informed consent was obtained before the patients were inducted into the study. The various WBC-derived ratios were calculated from the data collected and compared between the two subgroup populations as indicative of their inflammation and prognosis. Statistics were performed using SPSS software version 16. P-value≤0.05 was considered statistically significant. Results: The tuberculous patients with cavity were younger, and the absolute neutrophil counts (ANC), liver enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT), were significantly higher among the cavitatory group compared to noncavitatory group. Comparing inflammation between the groups showed statistically significant differences between the cavitatory and the non-cavitatory groups in most of the WBC-derived ratios. Conclusions: Most of the inflammatory indices serve as easy and inexpensive biomarkers. Their prognostic value allows risk stratification among PTB patients. These markers can be used to predict the outcomes as well as assess the response to treatment.